Characteristics of piRNAs and their comparative profiling in testes of sheep with different fertility - Di, Ran; Zhang, Rensen; Mwacharo, Joram Mwashigadi; Wang, Xiangyu; He, Xiaoyun; Liu, Yufang; Zhang, Jinlong; Gong, Yiming; Zhang, Xiaosheng; Chu, Mingxing (Frontiers in Genetics, 2022)
As a novel class of small RNAs, piRNAs are highly expressed in the animal gonad and their main known role is to inhibit transposon activity for ensuring the correctness and integrity of the genome. In order to explore the characteristics of piRNAs in sheep testis and their possible regulatory roles on male reproduction, deep sequencing technology was used to sequence small RNAs and identify piRNAs in the testes of sheep. The length of piRNAs in sheep testes showed a unimodal distribution between 26 and 31 nt, with a peak at 29 nt. These piRNAs exhibited obvious ping-pong signature and strand specificity. In the genome, they were mainly aligned to CDS, intron, repetitive sequence regions and unannotated regions. Furthermore, in transposon analysis, piRNAs were aligned predominantly to LINE, SINE, and LTR types of retrotransposon in sheep testes, and the piRNAs derived from each type showed obvious ping-pong signature. The piRNA clusters identified in sheep testes were mainly distributed on chromosomes 3, 7, 15, 17, 18 and 20. The results combining semen determination with pathway enrichment analysis implied that differentially expressed piRNAs between the testes of rams with different fertility may participate in spermatogenesis by regulating multiple pathways closely related to stabilization of blood-testis barrier and renewal and differentiation of spermatogonial stem cell. Taken together, the study provided new insights into the characteristics, origin and expression patterns of piRNAs in sheep testes tissue, which would help us better understand the role of piRNAs in sheep reproduction.